Análise e caracterização de ataques a rebanhos por morcegos Desmodus rotundus no município de São Pedro (São Paulo, Brasil) - Mialhe, Paulo Jacques (2010)
In the present study were analyzed and characterized the attacks on herds of livestock by vampire bats Desmodus rotundus in São Pedro (São Paulo, Brazil). It was found that the frequency of attacks of Desmodus rotundus to domestic herbivores in São Pedro-SP during the study period, between 2000 and 2001 was 4.2%, but may have been underestimated due to the extensive management system used for cattle, which constitutes 90.07% of the total herd. In the properties they owned cattle and horses, and therefore with the same time searching for prey by bats because the same distance from the shelter to the properties, there was a higher percentage of attacks on horses in 90.47% of properties indicating the possibility Desmodus have as of this preferred prey animals. We identified nine main shelter of the vampire bat, these three were classified as maternity colonies, all located in caves, with higher numbers of individuals. It was shown that the main shelters Desmodus were closer than 3 km of the main water bodies of the study area, confirming other studies reporting that the major rivers of the state of São Paulo are the major geographical features related to the presence of Desmodus.